Production of muons from heavy flavor decays at forward rapidity in pp and Pb-pb collisions at √sNN=2.76 TeV - Abelev, Betty; Busch, Oliver; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lara Martinez, Camilo Ernesto; Lohner, Daniel; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physical review letters, 2012)
The ALICE Collaboration has measured the inclusive production of muons from heavy-flavor decays at forward rapidity, 2.5<y<4, in pp and Pb-Pb collisions at √sNN=2.76 TeV. The pt-differential inclusive cross section of muons from heavy-flavor decays in pp collisions is compared to perturbative QCD calculations. The nuclear modification factor is studied as a function of pt and collision centrality. A weak suppression is measured in peripheral collisions. In the most central collisions, a suppression of a factor of about 3-4 is observed in 6<pt<10 GeV/c. The suppression shows no significant pt dependence.